Production and Characterisation of Cyclodextrin Glycosyltransferase from a Locally Isolated Bacillus Sp - Ai Noi, Sauvaphap (2006)
Cyclodextrin glycosyltransferase (E.C.2.4.1.19) synthesise cyclic oligosaccharide which is also known as cyclodextrin, from starch. Most of the known CGTases produce a mixture of a-, B- and Y-CD at different ratios. CGTase producing microorganism was isolated from local soils on selective agar medium containing soluble starch which produced clear zones as qualitative measurement of the enzyme present. A total of 250 isolates were collected but only one isolate (Strain MK 6) was selected for further studies based on its highest activity. Strain MK 6 was identified as gram positive rod, motile and produced spore. Biochemical identification using API CHB/E medium confirmed the strain MK 6 was the Bacilllus sp with 85% similarities. CGTase isolated from alkalophilic Bacillus sp. was further characterized. Optimum activity obtained at temperature of 70oC and the enzyme shows a wide range of pH stability ranging from 4 -10 when stored at 4oC for 24 hours and temperature stability ranging from 30oC - 80oC at 1 h incubation period. The CGTase activity was even maintained at 0.4 U/ml at 90oC for 40 min incubation. Prior to optimisation of CGTase production, selection for the best carbon source through detection on modified phenolphthalein method containing different types of starch were performed. Sago starch gave significant result and was used for further optimisation using statistical analysis namely Response Surface Methodology (RSM). The optimal calculated values were 3.34% sago starch, initial pH of 10.15 and agitation speed of 187 rpm; with predicted activity of 2.07 U/ml of CGTase. These predicted optimal parameters were confirmed in the laboratory and the final CGTase activity obtained was very close to the predicted value at 2.56 U/ml. The optimised crude enzyme produced mainly y-CD (61.6% of the total cyclodextrin amount) with only y-CD as minimal product without detection of y-CD.